Persepsi Mahasiswa terhadap Problem Based Learning di Mata Kuliah Reading For Academic Purposes - Yunita Hatibie (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2025)
Problem Based Learning in Reading for Academic Purposes require students’ critical thinking to analyze, collaborate, engagement, solve the problem and self-directed study to the students. This research explored the students’ perception towards Problem Based Learning in Reading for Academic Purposes.  Descriptive qualitative approach is used in this research which used semi-structured interviews with  third-year  English  Department  students  who  had  Problem Based Learning in Reading for Academic Purposes. This research used Thematic  Analysis  to revealed  the  students’ perception on Problem Based Learning in Reading for Academic Purposes. It shown that students have positive perceptions of Problem Based Learning in Reading for Academic Purposes. Students reported that PBL is engaging and meaningfull approach to enhance Reading for Academic Purposes. PBL effectively  encourages  active  participation,  improves  text  comprehension,  and  fosters  learning  motivation through  relevant  and  meaningful  tasks.  Students perceive improvement in critical thinking, analysis, and the ability to solve complex problems within academic texts. Collaboration  within  groups  was  also  found  to  enhance  their communication  and  teamwork  skills.  Many students find group dynamics challenging, requiring strong facilitation to be effective. Supporting  factors  identified  include  the  use  of  authentic  reading materials,  opportunities  for  discussion  and  reflection,  and  the  instructor's  role  as  a  supportive  facilitator. Students appreciate when PBL is implemented with scaffolding, as they often face difficulties with the heavy workload, need for extensive outside research, and time management. Meanwhile, several challenges were also noted, such as limited learning time, uneven group contributions, varying reading abilities among group members, and difficulties in understanding academic vocabulary. Students feel more responsible for their own learning process, which boosts their confidence in tackling difficult academic materials. The findings  suggest  that  while  PBL  is  effective  in  enhancing  reading  for academic purposes  and  promoting  student-centered  learning,  its  successful  implementation  requires  careful  planning,  scaffolding  strategies,  and continuous support from instructors to overcome the identified constraints.